A Systematic Review of Interventions That Integrate Perinatal Mental Health Care Into Routine Maternal Care in Low- and Middle-Income Countries - Prom, Maria C.; Denduluri, Amrutha; Philpotts, Lisa L.; Rondon, Marta B.; Borba, Christina P. C.; Gelaye, Bizu; Byatt, Nancy (Frontiers in Psychiatry, 2022)
Background: Women in low- and middle-income countries (LMICs) are disproportionally affected by perinatal depression and anxiety and lack access to mental health care. Integrating perinatal mental health care into routine maternal care is recommended to address gaps in access to mental health care in such under-resourced settings. Understanding the effectiveness of interventions that integrate perinatal mental health care into routine maternal care in LMICs is critical to inform ongoing intervention development, implementation, and scale-up. This systematic review aims to assess the effectiveness of interventions that integrate perinatal mental health care into routine maternal care to improve maternal mental health and infant health outcomes in LMICs. Method: In accordance with the PRISMA guidelines, an electronic database search was conducted seeking publications of controlled trials examining interventions that aimed to integrate perinatal mental health care into routine maternal care in LMICs. Abstracts and full text articles were independently reviewed by two authors for inclusion utilizing Covidence Review Software. Data was extracted and narrative synthesis was conducted. Findings: Twenty studies met eligibility criteria from the initial search results of 2,382 unique citations. There was substantial heterogeneity between the study samples, intervention designs, and outcome assessments. Less than half of the studies focused on women with active depression or anxiety. Most studies (85%) implemented single intervention designs involving psychological, psychosocial, psychoeducational, or adjuvant emotion/stress management. There were few interventions utilizing multicomponent approaches, pharmacotherapy, or referral to mental health specialists. Outcome measures and assessment timing were highly variable. Eighteen studies demonstrated significantly greater improvement on depression and/or anxiety measures in the intervention group(s) as compared to control. Conclusion: Integrated interventions can be effective in LMICs. The findings provide a critical understanding of current interventions design gaps. This includes the lack of comprehensive intervention designs that incorporate increasing intensity of treatment for more severe illness, pharmacotherapy, mental health specialist referrals, and non-mental health professional training and supervision. The findings also provide strategies to overcome design and implementation barriers in LMICs. Study findings provide a foundation for future evidence-based adaptation, implementation, and scale-up of interventions that integrate perinatal mental health care into routine maternal care in LMICs.